2021
DOI: 10.1186/s12876-021-01895-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of hypoglycemia episode in cirrhotic patients during hospitalization

Abstract: Background Studies have shown that hyperglycemia in cirrhotic patients increases mortality. However, no population-based study has evaluated the influence of hypoglycemia upon hospital admission on death in these patients. The aim of this study was to assess the effect of hypoglycemia at admission on the mortality of patients with liver cirrhosis. Methods The Taiwan National Health Insurance Database was searched, and 636 cirrhotic patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Furthermore, our analysis identified CLD as a significant predictor of mortality. The occurrence of hypoglycaemia in the context of CLD is an established determinant of adverse outcomes 28 . However, how CLD can worsen prognosis in patients with IGF‐2‐mediated hypoglycaemia is not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our analysis identified CLD as a significant predictor of mortality. The occurrence of hypoglycaemia in the context of CLD is an established determinant of adverse outcomes 28 . However, how CLD can worsen prognosis in patients with IGF‐2‐mediated hypoglycaemia is not studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study found that glucose was a protective factor for in-hospital mortality in patients with cirrhosis combined with sepsis (OR = 0.996, 95% CI 0.994–0.998). This may be related to the fact that patients with cirrhosis have impaired liver function and insufficient hepatic glycogen reserve, which makes them prone to hypoglycemia 28 . Appropriate maintenance of a certain level of blood glucose helps to provide the body with the necessary energy support and reduces the metabolic burden on the liver, thus exerting a protective effect on such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate and multivariate analysis showed that the short-term prognosis of patients with hypoglycemia was significantly worse than that of patients without hypoglycemia. A study of 636 patients with decompensated cirrhosis without diabetes by Hung et al (18) found that the 30-day mortality of patients with hypoglycemia was as high as 30.2%. In contrast, the 30-day mortality of patients without hypoglycemia was only 7.4%, which was similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%